Pengaruh kompetensi kewirausahaan tehadap keberhasilan usaha pada UMKM - Utama, Dian Herdiana; Sulastri, Sulastri; Asiah, Nur (Journal of Business Management Education (JBME), 2023)
The study aims to obtain an overview of the magnitude of the direct and indirect influence and influence of entrepreneurial competence on business success. This research uses descriptive and verification methods with a quantitative approach. The variable that is endogenous is business success (Y), then discovery and pursuit of opportunities (X1), risk taking skills (X2) and managerial skills (X3) are exogenous variables. The population used in this research is Banana Chips MSMEs in Bandar Lampung. This sampling method uses purposive sampling, where the researcher determines the sampling by determining special characteristics that are in accordance with the research objectives so that it is hoped that they can answer the research problems. The verification data analysis technique used is path analysis using the IBM SPSS Statistics 25.0 for Windows program. The findings of this research indicate that the description of entrepreneurial competence on business success is in the quite good category. Entrepreneurial competence has a simultaneous positive and significant influence on business success